PENERAPAN METODE BERMAIN PERAN UNTUK MENINGKATKAN PEMBELAJARAN BAHASA INDONESIA ASPEK BERBICARA - Musa Ismail (Madah: Jurnal Bahasa dan Sastra, 2015)
Indonesian language (IN) is one of the obligatory lessons in Senior High School. The learning of Indonesian language is pointed to the increasing ability of students. This aim to increase students ability to communicate in Indonesian language well and properly. The communication ability is expected especially in oral and written. Besides, students are hoped to be able to appreciate literary works. The objective of this research is to identify and to describe the implementation of role play method in the efforts to increase the activity of Indonesian language learning in speaking aspects and to identify and to get the description whether  the implementation of the method can increase process and result speaking aspect of Indonesian language learning of students class XI IPS 1, Semester 1, SMAN 3 Bengkalis. The method used was classroom action method and the subject was class XII IPS 1, semester 1, SMAN 3 Bengkalis. The collection of data and information were carried out by observation, journal and document study. The result of the research showed that (1) The implementation of of role play method can increase the activities of speaking aspects in  Indonesian language  learning. On the  1st cycle1, 1st meeting, the percentage of students activities was 73% with the good category (3,6), while on the second meeting, it was 82% with the very good category (3,7). On the first meeting of the second cycle, the percentage of students activities became 83% with the very good category (4,3), while on the second meeting was 96% with the very good category (5,0), (2) The implementation of role play method is able to increase the result of speaking aspect in learning Indonesian language. On the first cycle, the students reserved effort was 73% while on the second cycle was 77%. Meanwhile, based on attachment 3, the classical completeness on cycle 1 reached 86%, on cycle 2, it increased 96%. Based on the result of the research, the researcher proposed that it would be better for the Indonesian language teachers to implement role play method for the materials that are suitable with speaking aspects. The reason is that this method is proved to be able to increase the process and result of students learning. When implementing this method, teachers are hoped to give guidance, motivation, and explanation that more focused so that students can learn optimally.